A portable system for phasor measurment units (PMU) calibration in high-voltage substations. (December 2021) - Slomovitz, Daniel; Trigo, Leonardo; García, Agustin; Izquierdo, Daniel; Faverio, Carlos; Sandler, Rogelio
Abstract: This paper presents the advances in the development of a portable PMU standard for online calibration of PMUs installed in high voltage substations. This system is intended to be connected in parallel with the PMU under test, without disconnecting it from the network. Current and voltage sensors do not need to interrupt the service. In this way, all the substation functions remain operational during the calibration process. The time stamp is also checked by the proposed system, using a common-view GPS system traceable to the Coordinated Universal Time (UTC).